Corrigendum: Exploring the social and economic consequences of the metaverse: a multi-criteria approach to the SDGs - Ghasemzadeh, Fatemeh; Ghahremannasab, Babak; Antuchevičienė, Jurgita; Šniokienė, Violeta (Technological and Economic Development of Economy, 2025)
Fatemeh Ghasemzadeh, Babak Ghahremannasab, Jurgita Antuchevičienė, Violeta Šniokienė, authors of the article “Exploring the social and economic consequences of the metaverse: a multi-criteria approach to the SDGs”, published in Technological and Economic Development of Economy, 31(5), 1619–1643, https://doi.org/10.3846/tede.2025.24858 inform that the first author's last name is misspelt and we would like to make the following correction to the authorship:Fatemeh GHASEMZADEH, Babak GHAHREMANNASAB, Jurgita ANTUCHEVIČIENĖ, Violeta ŠNIOKIENĖThe authors regret the error.